Marketing Concept of Strategic Management of Competitiveness of Industrial and Commercial Activity of Subsidiaries of Agricultural Enterprises - Lyudmyla Lomovskykh; Nataliya Iefremova; Olena Kovalova (Науковий вісник Мукачівського державного університету. Серія Економіка, 2019)
To date, the need for strategic management of the competitiveness of production and commercial activities of agricultural entrepreneurship actors is due to the process of economic development and one of its main goals is to increase the efficiency of the functioning of the subjects of agrarian entrepreneurship. The article is devoted to the actual problem about the process of strategic management of the competitiveness of business entities on marketing principles. The purpose of the article is to substantiate the importance of introducing marketing approaches in the process of strategic management of the competitiveness of production and commercial activity of subjects of agrarian entrepreneurship. Scientific novelty consists in theoretical substantiation and combination of issues of strategic management, marketing, and management of competitiveness in the field of agrarian entrepreneurship. The relationship between these terms has been studied. To date, in the conditions of a modern market economy, in the presence and operation of marketing tools, such as systems of strategic management of production and commercial activities of subjects of agrarian business, strategic management of competitiveness can be an effective means of managing entrepreneurial activity in general. Modern direction of the principles of entrepreneurial activity tends to the marketing aspects: ways of increasing the efficiency of activity of production subjects and commercial activity of agrarian entrepreneurship, as well as increase of indicators of their competitiveness, should be based on modern marketing approaches. It has been determined that the marketing orientation of the management of the competitiveness of the enterprise's production and commercial activities means achieving the objective of the functioning of the subjects of agribusiness by market methods; a characteristic of the thinking style of managerial and administrative personnel, corporate culture, systems of universally recognized norms and values that are the basis for the formation of the principles of strategic management of competitiveness. Marketing orientation implies constant work on the support of the competitiveness of the proposal, and in the long term - the entire subject of production and commercial activity. It has been established that the main elements that are included in the concept of marketing orientation of the subject of production and commercial activity of subjects of agrarian entrepreneurship are ideological, instrumental, informational, organizational, process, target, and their functioning can be carried out with the help of managerial, distribution and functional types of marketing. The practical significance of the results obtained is that they can be used to develop a strategy for managing the competitiveness of production and commercial activities of agricultural entrepreneurship subjects on a marketing basis